A Self‐Anchored Phosphotungstic Acid Hybrid Proton Exchange Membrane Achieved via One‐Step Synthesis. Issue 17 (29th July 2014) - Lu, Shanfu; Xu, Xin; Zhang, Jin; Peng, Sikan; Liang, Dawei; Wang, Haining; Xiang, Yan
<x xml:space="preserve">Abstract</x> An excellent hybrid proton exchange membrane (PEM) is prepared using a one‐step synthesis to anchor phosphotungstic acid (HPW) into a polyvinylpyrrolidone (PVP) matrix. The hybrid membrane exhibits high proton conductivity and excellent stability. The impressive performance of a single cell based on the hybrid membrane, with a power density of 618 mW cm–2 at 50 °C, demonstrates promising potential for application in fuel cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>